2020
DOI: 10.1016/j.jaim.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of herbal extract of Acacia arabica with triphala on the biofilm forming cariogenic microorganisms

Abstract: Background Dental caries is a biofilm-related infectious disease with a multifactorial etiology, over five billion inhabitants have affected worldwide due to this disease. Objective Antimicrobial efficacy of a mixed herbal powder extract (MHPE) against cariogenic microorganisms was investigated. Materials and methods MIC, MBC, kinetics of killing, biofilm disruption and anticaries effect of MHPE were determined. For biofilm disruption, biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Based on the inclusion and exclusion criteria, a total of 31 studies are presented and analyzed in this comprehensive review. Table 1 records the in vitro studies conducted from 2019 until 2024 [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], and Table 2 analyzes the in vivo, in situ, and ex vivo clinical studies available in the literature [ 74 , 75 , 76 , 77 , 78 , 79 ]. In both tables, extensive descriptive information on the aim of the study (objectives), the type of experimental and control groups used, the methodological pattern followed, the bacterial strains chosen, and the results that emerged is present.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the inclusion and exclusion criteria, a total of 31 studies are presented and analyzed in this comprehensive review. Table 1 records the in vitro studies conducted from 2019 until 2024 [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], and Table 2 analyzes the in vivo, in situ, and ex vivo clinical studies available in the literature [ 74 , 75 , 76 , 77 , 78 , 79 ]. In both tables, extensive descriptive information on the aim of the study (objectives), the type of experimental and control groups used, the methodological pattern followed, the bacterial strains chosen, and the results that emerged is present.…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 ] Hence, to overcome and reduce such side effects, different studies have been evaluated the anti-microbial and anti-biofilm effects of various herbal extracts. [ 6 7 21 22 ] Since dental plaque formation as a biofilm initiates with the adherence of bacteria ( S. mutans ) to the pellicle and in situ growth of attached cells, finding herbal agents with the anti-adherence activity along with anti-microbial property can possess a beneficial role in preventing biofilm and caries development. Although P. atlantica species are considered the best known and one of the most appreciated medicinal plants in countries like Iran, Turkey, etc., still very few studies regarding its anti-cariogenic potential are available in literatures.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there are some well-known anti-microbial agents like chlorhexidine gluconate (CHX) which is very successful in reducing the salivary mutans Streptococci count, but it is not effective as a preventive agent due to its adverse effects like teeth and tongue discoloration and bacterial resistance. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…There are increasing numbers of reports that suggest the biofilm disruption activity of herb extracts [ 28 ]. In a study by Ramalingam et al [ 29 ], mixtures of Acacia arabica and triphala extracts were tested for their biofilm disruption activity against A. viscosus , C. albicans , L. casei , and S. mutans . The results revealed that the extracts, at a concentration of 150 µg/mL, not only reduced the biofilm by 91–99% but also prevented bacterial adhesion, thus stressing that they can act as effective anti-caries agents.…”
Section: Herbal Remedies For Dental Diseasesmentioning
confidence: 99%